PENGARUH KOMPETENSI, KOMPENSASI, IKLIM ORGANISASI DAN ETOS KERJA PUSTAKAWAN TERHADAP KINERJA PUSTAKAWAN PERPUSTAKAAN PERGURUAN TINGGI DI KOTA BANDAR LAMPUNG - Rd. Erni Fitriani; Bambang Utoyo Sutiyoso; Nur Effendi (Wacana Publik, 2018)
Generally librarian library public universities in the City of Bandar Lampung proposes to increases fungctional position of librarian over two years. This indicates that the performance of the librarian still low. The low performance of the librarian thought to be caused by several factors that influence. The purpose of this study are 1) to analyze and review the influence of competency to librarian performance, 2) analyze and review the influence of compensation to librarian performance; 3) analyze and review the infuence of organizational climate to librarian performance; 4) analyze and review of the influence of the work ethic to librarian performance; 5) analyze and review of the influence of competence, compensation, organizational climate and work ethic of librarian performance at state college library in Bandar Lampung. The type of this research is to descriptive and verification that describe the variables that the object of research, namely competence, compensation, organizational climate and work ethic to librarians performance and test the truth of a hypothesis through data collection in the field. The method used in this research is quantitative with total sampling technique. The collection of data through primary data and secondary data, using a Likert scale. Mechanical testing of the instrument through the validity and reliabilty test Data analysis using descriptive analysis and inferential analysis with data processing using SPSS. Hypothesis testing with multiple linear regression test classic assumptions include partial t-test and f-simultaneous test, test the coefficient of determination (R2), the normality test and heterokedatisitas multikorelasi test. The results of this study is partially competence influential is 65.4% to librarian performance, compensation influential is 62.6% to librarian performance, climate organizations influential is 59,4% to librarian performance and work ethic influential is 53% to librarian performance, simultaneously competence, compensation, organizational climate and work ethic take influence are 88,9% to librarian performance of University Library in the city of Bandar Lampung